MERCs. The Novel Assistant to Neurotransmission? - Shirokova, Olesya M.; Pchelin, Pavel V.; Mukhina, Irina V. (Frontiers in Neuroscience, 2020)
In neuroscience, much attention is paid to intercellular interactions, in particular, to synapses. However, many researchers do not pay due attention to the contribution of intracellular contacts to the work of intercellular interactions. Nevertheless, along with synapses, intracellular contacts also have complex organization and a tremendous number of regulatory elements. Mitochondria-endoplasmic reticulum contacts (MERCs) are a specific site of interaction between the two organelles; they provide a basis for a large number of cellular functions, such as calcium homeostasis, lipid metabolism, autophagy, and apoptosis. Despite the presence of these contacts in various parts of neurons and glial cells, it is yet not known whether they fulfill the same functions. There are still many unsolved questions about the work of these intracellular contacts, and one of the most important among them is if MERCs, with their broad implication into synaptic events, can be considered the assistant to neurotransmission?